Organic matter removal from a membrane bioreactor effluent for reverse osmosis fouling mitigation by microgranular adsorptive filtration system - Chun, Youngpil (2022)
In this study, a prototype microgranular adsorptive filtration (μGAF) system was constructed employing a 7-bore ceramic membrane as the primary membrane and either heated aluminum oxide particles (HAOPs) or powdered activated carbon (PAC) as the pre-deposited dynamic membrane (DM). The system was used to pre-treat membrane bioreactor (MBR) effluent from a full-scale MBR-reverse osmosis (RO) water reclamation plant. The downstream RO performance and membrane fouling potential of the treated effluent were then assessed. The results indicated that: (i) although PAC removed more overall EfOM than HAOPs did, HAOPs were more effective in removing biopolymers such as polysaccharides and proteins, (ii) HAOPs virtually eliminated fouling of the primary ceramic membrane, whereas considerable fouling (much of it irreversible) occurred when the feed was pretreated with PAC, (iii) HAOPs removed more than 90% of the phosphorus and fluoride from the feed, but PAC removed negligible amounts of these contaminants, and (iv) HAOPs-treated effluent resulted in only a 43% decline in RO permeate water flux over 5 d of continuous filtration, as opposed to 62% flux decline for untreated or PAC-treated effluent. This study thus demonstrates the effectiveness of the HAOPs-based μGAF process as a pre-treatment for improving downstream RO recovery.